MACRO-ECONOMIC INDICATORS OF NON-PERFORMING LOANS: A COMPARATIVE STUDY OF PAKISTAN AND INDIA (2012-2016) - Ghafoor Kazi, Abdul; Kazi, Shazia; Nabi Baksh, Marium (International Journal of Psychosocial Rehabilitation, 2020)
Many countries around the world face countless financial crises, and sometimes the reason for such crisis is a Non-performing Loan (NPL). A loan is considered as non-performing if it is default or closed to being in default. It occurs when the borrower defaults and as a result, banks show this loss as a bad debt in the financial statements. These loans reduce the growth and strength of banks and in return, financial instability is developed. On the other hand the in Sovereign debt, money supply, and unemployment has increased the NPLs. In the field of quantitative research it was essential for us to collect the data and analyze its influence on NPLs using the current data rather than using the old data and predicting our results on basis of past trends. This research attempts to analyze the effects of four macroeconomic indicators namely foreign direct investment (FDI), money supply, sovereign debt and unemployment and using the Non-performing loans of a country as the barometer. This research performs linear regression using the NPL as our dependent variable and FDI, money supply, sovereign debt and unemployment as independent variables (predictors). The sources of secondary data were the websites of the World Bank and State Bank of Pakistan; the website of State Bank of India was also used. The data of NPL clearly gave us the idea about two different economies and guided us to compare their results and to find conclusion to our study. The result of the data can be of immense use in future to analyze the factors affecting the NPL in different economies.Keywords--  ,  ,